The Importance of Blood Pressure Control in End-Stage Renal Disease: A Case Report of Intracranial Hemorrhage - Hamid Faqih Umam; Nova Nasikhatussoraya; Shofa Chasani; Durrotul Djannah (Nusantara Science and Technology Proceedings, 2024)
Introduction: End-Stage Renal Disease (ESRD) is a growing global health concern. ESRD often presents with high blood pressure that is unresponsive to medication. Long-standing high blood pressure is the primary cause of intracranial hemorrhage. It is more likely to occur in ESRD patients. Case Illustration: A 69-year-old woman was brought to the emergency room because of unconsciousness four hours earlier. She had a sudden severe headache before that. No history of trauma. Her consciousness was poor (GCS E1M2V1) and her blood pressure was high (213/78 mmHg) in the emergency unit. Head CT revealed intracerebral, intraventricular, and subarachnoid hemorrhages with a total volume of 81 cc and midline shift. The patient had been on dialysis twice a week for six years. She had uncontrolled hypertension said to routinely take antihypertensive drugs independently. Last year's dialysis visits showed high blood pressure, with a mean of 187/72 mmHg (224/112-166/51 mmHg). Given her complex condition, she underwent conservative therapy and died on the third day of treatment. Conclusion: ESRD patients are at high risk of intracranial hemorrhage. It is crucial to closely monitor blood pressure during dialysis visits. ESRD with intracranial hemorrhage has a poor prognosis, emphasizing the importance of preventive care.